Interactive game application of cooking Malay traditional cuisines toward teenagers in Malaysia / Anis Najwa Rosli and Ahmad Sofiyuddin Mohd Shuib - Rosli, Anis Najwa; Mohd Shuib, Ahmad Sofiyuddin (Universiti Teknologi MARA, Perak, 2020)
The proposed interactive game application of cooking Malay traditional cuisines is a game designed to teach teenagers aged 12 to 24 years old in the cooking. There were a bunch of interactives cooking game applications on the internet, except for Malay cuisine games. This game is created to attract teenagers to making Malay traditional cuisine in interactive and fun ways. In this game, the user needs to follow the storyline in the game. Then, in the early game, they were given a list of ingredients to make some Malay cuisines. The player will be given the customer's requested food picture. Then the players need to click the right ingredients in making of the requested food by customer. If the player picks the wrong ingredients, then need to pick the ingredients from the start again. Next, this game concept is casual. With the time given, the players need to complete the order with minimum specific score to move forward to next stage. If they achieve the best result, the player will gain extra money and extra time bonus in the game. This game created with a different type of menus based on every chapter of the story. This game can attract teenagers to learn about cooking and the ingredients used in the food. This game is created to educate teenager yet entertain them at the same time.